Swallow patterns associated with aspiration in COPD: a prospective analysis. Issue 3 (26th July 2021) - Cvejic, Lydia; Guiney, Nadine; Lau, Kenneth K.; Finlay, Paul; Hamza, Kais; Leong, Paul; MacDonald, Martin; King, Paul T.; Bardin, Philip G.
Aspiration during swallow may have devastating consequences in COPD. It is known that COPD can impair swallow efficiency and safety [1–3] and a better understanding of how patients with COPD swallow is essential to inform preventative strategies. To date, no studies have examined swallow of large liquid volumes representative of everyday fast-paced drinking in an ample number of patients with COPD. In this letter we detail swallow patterns evaluated by videofluoroscopy in patients with COPD, with and without evidence of aspiration. Few studies have examined swallow of large liquid volumes representative of everyday drinking in COPD. Swallow by cup-drinking was evaluated in COPD using videofluoroscopy. Slower swallow was linked to aspiration indicating altered swallow habits in COPD. https://bit.ly/3wpdnO3